Mathematical modeling for optimizing the blood supply chain network - Amir Rahimzadeh Dehaghani; Muhammad Nawaz; Rohullah Sultanie; Tawiah Kwatekwei Quartey-Papafio (Modern Supply Chain Research and Applications, 2021)
Purpose - This research studies a location-allocation problem considering the m/m/m/k queue model in the blood supply chain network. This supply chain includes three levels of suppliers or donors, main blood centers (laboratories for separation, storage and distribution centers) and demand centers (hospitals and private clinics). Moreover, the proposed model is a multi-objective model including minimizing the total cost of the blood supply chain (the cost of unmet demand and inventory spoilage, the cost of transport between collection centers and the main centers of blood), minimizing the waiting time of donors in blood donating mobile centers, and minimizing the establishment of mobile centers in potential places. Design/methodology/approach - Since the problem is multi-objective and NP-Hard, the heuristic algorithm NSGA-II is proposed for Pareto solutions and then the estimation of the parameters of the algorithm is described using the design of experiments. According to the review of the previous research, there are a few pieces of research in the blood supply chain in the field of design queue models and there were few works that tried to use these concepts for designing the blood supply chain networks. Also, in former research, the uncertainty in the number of donors, and also the importance of blood donors has not been considered. Findings - A novel mathematical model guided by the theory of linear programming has been proposed that can help health-care administrators in optimizing the blood supply chain networks. Originality/value - By building upon solid literature and theory, the current study proposes a novel model for improving the supply chain of blood.
Keywords: 650; Blood products; Blood supply chain; Location-allocation problem; NSGA-II; Queuing theory